Perlindungan Anak Terhadap Kekerasan Seksual Dimedia Social pada lingkungan Sekolah - Basrowi; Galuh (Qalam : Jurnal Ilmu Kependidikan, 2024)
Sexual violence on social media is a serious threat to children, especially in the school environment which should be a safe and child-friendly space. Lack of digital literacy, weak monitoring systems, and students' ignorance of forms of online sexual violence cause many cases to go undetected or unreported. This study aims to explore the forms of sexual violence experienced by students through social media and the role of schools, parents, and the community in protection efforts. The method used is a descriptive qualitative approach at SMPIT Bait Et-Tauhid school with data collection techniques through in-depth interviews, observations, and documentation of teachers, students, principals, and parents. The results of the study show that sexual violence occurs in the form of obscene messages, requests for personal content, to verbal harassment that is often considered trivial. The role of parents and schools is still limited to general supervision without adequate digital education. The community also tends to be unresponsive to the issue of online sexual violence. This study emphasizes the importance of collaboration between parties and strengthening digital literacy to build an effective child protection system, in line with the mandate of Law No. 35 of 2014 concerning Child Protection and the ITE Law in creating a safe digital environment in the Society 5.0 era.